Modulation of Arabidopsis growth by volatile organic compounds from a root-derived bacterial community - Türksoy, Gözde Merve; Carron, Rejane; Koprivova, Anna; Kopriva, Stanislav; Wippel, Kathrin; Tonni Grube Andersen (bioRxiv, 2022)
Plant roots are surrounded by fluctuating biotic and abiotic factors. The living component the microbiota is actively shaped by the plant and plays an important role in overall plant health. While it has been shown that specialized metabolites exuded from the plant are involved in shaping host interactions with the microbiota, it is unclear how underground volatile organic compounds (VOCs) influence this communication. This is especially true for root-associated bacteria which are known to release VOCs that can influence plant growth. Using a simplified synthetic bacterial community (SynCom) representing the phylogenetic diversity of bacteria in the root microbiome, we set out to characterize plant growth and defense metabolites when subjected to bacterial VOCs (bVOCs). Moreover, by profiling the SynCom community composition after co-cultivation with the plant, we explored how members of the community influenced each other in our growth setup. Our findings reveal that plant growth promotion can occur via VOCs from a bacterial SynCom, but that the plant response differs for individual community members. In addition, we find that bVOCs are able to repress chemical defense responses in the plant, possibly to facilitate colonization. By removing key species from the SynCom, we find that complex bacteria-bacteria interactions are likely to underlie this phenomenon, and that bVOC-induced modulation of plant responses in the rhizosphere may be an emergent property of bacterial communities rather than depending on individual species. Competing Interest Statement The authors have declared no competing interest.